Deciphering the offensive process in women's elite football: A multivariate study - Maneiro, R.; Iván-Baragaño, I.; Losada, J. L.; Ardá, A. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Over the last few years, there has been considerable increase in scientific knowledge about women's football. However, the tactical and tactical-strategic aspects have not yet been sufficiently covered in scientific literature. Therefore, this work proposed the following aims: To describe how the offensive phase is produced in women's football, to identify the significant statistical criteria that may be modulating success in attack, and finally to propose different predictive success models, with the ultimate aim of passing this knowledge on to the applied field. The observational methodology was used, one of the most appropriate methodologies for the analysis of motor behaviors in sport. The units of analysis collected and analyzed were 6063 attacks carried out during the FIFA Women's World Cup Canada 2015 and France 2019. The available results demonstrate that, on the one hand, offensive team actions are ineffective (almost 70% finish unsuccessfully), but criteria such as the start form of the attack, zone of ball possession, partial match result, or ball possession time are statistically significant criteria that modulate attack success (goal, shot or pass into the area). Lastly, the multivariate results allow us to propose a theoretical model, passing the probability of success from 31% in the absence of a model, to a theoretical auction probability of 52.6%, based on fast attacks with the intervention of few players, and with possession zone in the opposite field. These results could be directly transferred to the practical field where trainers and technical bodies can put this information into practice in training sessions or matches.